Catalytic cracking of waste cooking oil followed with hydro-isomerization for high-quality biofuel production. (15th April 2022) - Jiang, Xia; Long, Feng; Cao, Xincheng; Zhao, Jiaping; Liu, Peng; Xu, Junming
Abstract: Desulfurization and molecular structural modification are critical steps for producing high-quality biofuel. Here, we demonstrated an efficient and environmentally desulfurization process for converting waste cooking oil containing many impurities to low-sulfur biofuel, and this production process could be adopted on a large scale. This study found that composite catalysts (10 wt% base catalyst and 1 wt% cupric nitrate) could effectively remove the impurities (sulfur, chlorine and metal ions) in waste cooking oil during the deoxygenation process. The desulfurization rate was achieved at 94% over Cu(NO3 )3 and K2 CO3 (1 wt%:10 wt%). The copper nitrate catalyst converted sulfur species into water and H2 S. In addition, to further obtain high-quality biofuel with low cold flow property, the above generated biofuel with low sulfur content was hydro-isomerized over the Ce–Pt/SAPO-11 catalyst. Under the action of the bimetallic catalyst, the isomerization reaction could be carried out at low reaction temperature (300 °C) due to the high olefin content (approximately 43%) in pyrolytic oils. A high-quality biofuel production with low sulfur content (lower 10 ppm) and low cold filter plugging point (−20 °C) could be obtained through the above two processes, which all met the ASTM and EN specifications. Overall, a novel method was reported to convert low-quality waste cooking oil to high valuable biofuel. Highlights: The sulfides in waste cooking oil are removed via a facile method. A novel process is developed to convert waste oil to high-quality biofuel, which satisfied the requirement ASTM D6751 and EN 14214. This approach is a suitable technology for converting the waste oil with high amount of impurities, high viscosity, and waster content. The removal of metal ions and chlorine-containing compounds in waste oil are studied. The isomerization reaction temperature can be reduced to 300 °C.